The effectiveness of employment vouchers: a simple approach - Jonathan Michael Orszag; Dennis J. Snower (German economic review, 2000)
This paper explores the optimal design of subsidies for hiring unemployed workers ('employment vouchers' for short) in the context of a dynamic model of the labor market. Focusing on the short-term and long-term effects of the vouchers on employment and unemployment, the analysis shows how the optimal policy depends on the rates of hiring and firing, and on the problems of displacement and deadweight. It also examines the roles of the government budget constraint and of the level of unemployment benefits in optimal policy design. We calibrate the model and evaluate the effectiveness of employment vouchers in reducing unemployment for a wide range of feasible parameters.
Keywords: 330; Employment policy; unemployment benefits; government budget constraint; Arbeitsmarkttheorie; Subvention; Personalbeschaffung; Haushaltsdefizit; Theorie